Design, elaboration and characterization of a Ni-MH battery prototype - Cuscueta, Diego Javier (2010)
This paper shows advances achieved in the design and construction of a nickel emetal hydride (Ni-MH) battery prototype. The requirements of the design were to characterize the new variables appearing in a commercially assembled battery, such as limited physical space, electrical contact resistance, the behaviour of the system as a function of the gas evolution during fast charge and overcharge, and others. The electrochemical characterization was performed using laboratory equipment. In the ﬁrst design version an anode and a cathode, both embedded in electrolyte, and electrically isolated by means of a separator, were placed inside a reactor. Based on the identiﬁcation of problems detected in the structural performance analysis and the electrochemical characterization of the different prototype models, the versatility and usefulness of the designs were optimized. The ﬁnal prototype design was satisfactorily tested in electrochemical cycling and rate capability studies, with different electrode and separator materials and using different weights between electrodes. The internal pressure monitoring of a sealed cell, under different conditions of use, was also demonstrated, thus proving that the design allows the systematic study of different application requirements.